On the order of growth of rectangular partial sums of double orthogonal series - Andrienko, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We obtain estimates of the order of growth of rectangular partial sums of double orthogonal series and establish their unimprovability on the set of all double orthogonal systems.